1964
DOI: 10.1063/1.3051798
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of high-polymer physics: A survey and forecast

Abstract: The twentieth anniversary of the founding of the Division of High-Polymer Physics of the American Physical Society is an appropriate time to review the progress of polymer physics over the last two decades, and to re-evaluate the hopes of the founders and the present need for the Division. The continuing need for our Division perhaps is best shown by the fact that each of the last two meetings have set new records for the number of papers presented. Much of this progress is due to the officers who have contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Proceeding as before, it can be shown that this implies: shows this quite clearly• According to (6.2a), this implies that n~' monotonically increases towards the wall, and figure 5 shows a sample calculation. The result is at odds with basic thermodynamic arguments [4], and we are not aware of any experiments which 13) In this connection, recall the remarks following eq. (2.16).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Proceeding as before, it can be shown that this implies: shows this quite clearly• According to (6.2a), this implies that n~' monotonically increases towards the wall, and figure 5 shows a sample calculation. The result is at odds with basic thermodynamic arguments [4], and we are not aware of any experiments which 13) In this connection, recall the remarks following eq. (2.16).…”
Section: Discussionmentioning
confidence: 77%
“…Here (6h)) denotes the expectation value of the vector /@, while the diffusion dyadic D is defined by (note that Br is a symmetric dyadic) 4) n D= kTS d3 X BTv. respectively, means that we admit only the dumbbells which -at least in some average sense -are slender.…”
Section: R~8)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well known that the external shear field shifts the apparent phase diagram and strongly affects spinodal decomposition [ 19,[14][15][16], this kind of viscoelastic effect due to the self-induced, internal velocity field has never been considered, and further theoretical studies are necessary to clarify the effect and to establish this concept. There are many possibilities for new effects: for example, the local velocity field induced by phase separation might shift the local critical temperature during the phase separation.…”
Section: Dynamic Phase Diagrammentioning
confidence: 99%
“…Historically, the first notice about polymer melt spontaneously fractionating during flow under inhomogeneous stresses in capillary was presented in 1964 by Busse [1]. On the theoretical level he claimed that "capillary viscometer should tend to fractionate polymer molecules with respect to molecular weight along the radius of the capillary."…”
Section: Introductionmentioning
confidence: 99%